Asuhan Keperawatan Pada Ny. M dengan Intervensi Range of Motion Aktif Kaki terhadap Penurunan Kadar glukosa Darah dan Risiko Ulkus Pada Penderita Diabetes Melitus - Nurnidawati; Diani, Noor (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
Background: Diabetes Melitus is a serious threat to global health characterized by high blood glucose caused by the body's inability to produce insulin. One of the pillars of controlling the percentage level of blood sugar levels is carried out through the implementation of physical activity. Range of motion active feet is one form of physical exercise that can be done by patients with diabetes mellitus. Objective: This study aimed to determine the effect of active Range of Motion of the feet on reducing blood sugar levels and the risk of diabetic ulcers in clients with Diabetes Melitus.